2009
DOI: 10.1111/j.1541-4337.2009.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Pectins in Processed Fruits and Vegetables: Part II—Structure–Function Relationships

Abstract: Pectin represents a very heterogeneous biopolymer whose functionality remains largely puzzling. The link between the pectin fine structure and functional properties with relevance to plant growth and development, as well as food processing, is continually being explored. This review describes the current knowledge of pectin structure-function relationships. Key mechanisms dictating pectin structure-function relationships are discussed, including the polymer biosynthesis, cross-linking mechanisms, enzymatic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
163
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(176 citation statements)
references
References 260 publications
1
163
0
5
Order By: Relevance
“…This may be due to structure of plant tissue was opened and loosen through β-sheet destruction during blanching process [20] as explained in Figure 2. Ando et al [21] reported that the pectins in the middle lamella were leached away thereafter, adhesion of the cell walls was weakened, and the tissue was markedly softened [20]. Furthermore, the blanching process can denature the proteins in cell walls and make the porosity of membranes.…”
Section: Results and Discussion Proximate Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to structure of plant tissue was opened and loosen through β-sheet destruction during blanching process [20] as explained in Figure 2. Ando et al [21] reported that the pectins in the middle lamella were leached away thereafter, adhesion of the cell walls was weakened, and the tissue was markedly softened [20]. Furthermore, the blanching process can denature the proteins in cell walls and make the porosity of membranes.…”
Section: Results and Discussion Proximate Compositionmentioning
confidence: 99%
“…The surface morphology of the C. porrectum non-pretreated and pre-treated powder were investigated using a scanning electron microscope, Quanta 400 (FEI, Czech Republic) at high voltage 20.00 kV at 500x magnification. …”
Section: Structure Of Powder Determination By Scanning Electron Micromentioning
confidence: 99%
“…High-methoxyl pectin has 450% DE and form viscous gels in the stomach at pH 2.2-3.5 (Ralet et al, 1994;Sila et al, 2009). Low-methoxyl pectin has o50% DE.…”
Section: Pectin Types and Processingmentioning
confidence: 99%
“…In particular, in contrast to the composite prepared in Tris-buffered saline (TBS) at pH 7.6, ∼1.4-to 1.5-fold lower shear strengths were reached by the cases prepared at pH 4 or 9 after 7 d. Given that the cross-linking extent of the ivy-mimetic adhesive constructs is determined by the calcium-modulated electrostatic interaction that is susceptible to pH variations, it is reasonable to expect this pH-responsive event here. Because the pK a of pectin is ∼3.5 (60,61), and the isoelectric point of the AGP-rich ivy nanoparticles should be located in the acidic range given their negative charge displayed under neutral condition (Fig. 1E), the deprotonation of the carboxyl groups of the uronic acid residues within both components is suppressed at pH 4 in contrast to that in a neutral environment, resulting in less surface charge and thus weaker electrostatic interactions with calcium ions.…”
Section: Resultsmentioning
confidence: 99%